Os saberes da mediação humana em centros de ciências: contribuições à formação inicial de professores - Ovigli, Daniel Fernando Bovolenta (2009)
The theme of education in museums and science centers is still not present in initial training of science teachers. As the school context, the out-of-school spaces can also contribute to teacher training, especially for those students that are working in the mediation of scientific exhibitions during undergraduate studies. This work focuses on this theme by the study of knowledges mobilized by future teachers when the mediation activity in a science center and the possible relations between teacher knowledges (TARDIF, 2002) and human mediation knowledges in science centers (QUEIROZ et al., 2002) and the contributions of experience in museums for science teachers training. Semi-structured interviews and observations of visitor-mediator interactions integrated data collection, developed with six undergraduate students that are mediators, components of the Scientific Exhibition mediation team of Center for Scientific and Cultural Dissemination (CDCC) and the Interactive Space of Center for Structural and Molecular Biotechnology (CBME), both linked to the University of São Paulo, in São Carlos city. This is a qualitative research, and the empirical material was subjected to discursive textual analysis process. Four categories were outlined from the analysis of empirical data: (i) training in undergraduate course to act in the science center, (ii) views on education in museums and science centers, (iii) the human mediation knowledges and (iv) contributions to undergraduate teachers training. The results suggest that skills and abilities, characteristics of mediation activity have been expressed by different elements built by mediators to deal with unpredictable situations that occur in their practice, validating them as potential tools for science teachers training. It was found that these mediators, future teachers, play their role in museum mobilizing theoretical elements previously studied in undergraduate courses and making use of creativity in working with new situations, always present because of the unpredictability of mediations in museums and science centers. The possible implications of this research includes the links between education in museums and science centers and teachers training as well the ways that this subject can be worked in initial teachers training, including a partnership museum/school/university.